Enhanced removal performance and mechanistic study of Cu2+, Cd2+, and Pb2+ by magnetic layered double hydroxide nanosheets assembled on graphene oxide. (August 2022) - Li, Jing; Huang, Qiqi; Yu, Haiqin; Yan, Liangguo
Abstract: Devising effective measures for removing heavy metals from water has become a serious concern. In this study, MgAl-layered double hydroxide nanosheets were assembled on graphene oxide (GL) and its magnetic product (Fe3 O4 @GL) as excellent adsorbents for Cu 2+, Cd 2+, and Pb 2+ and were synthesized by a simple hydrothermal method. The morphology and surface chemical properties were observed to establish the construct-activity relationships. The characterization results showed that the adsorbents combined rich functional groups with large specific surface areas. The effective removal of heavy metals by GL and Fe3 O4 @GL was achieved under neutral and weakly alkaline conditions. The pseudo-second-order kinetic equation described the experimental results well, and the equilibrium data were in good agreement with the Freundlich model for Cu 2+ and Cd 2+ and the Langmuir model for Pb 2+ . The maximum adsorption capacity of GL (Cu 2+ : 89.26 mg/g, Cd 2+ : 76.67 mg/g, Pb 2+ : 226.98 mg/g) was slightly larger than that of Fe3 O4 @GL (Cu 2+ : 80.72 mg/g, Cd 2+ : 70.26 mg/g, Pb 2+ : 213.96 mg/g). The main mechanisms include the surface complexation of hydroxyl groups, precipitation reactions of metal hydroxides and metal carbonates, and isomorphic substitution of divalent metal cations. Thus, the enhanced adsorption capacity and mechanistic study provide new insights into the environmental remediation of heavy metals. Graphical abstract: Unlabelled Image